Insight into the herbicide resistance patterns in Lolium rigidum populations in Tunisian and Moroccan wheat regions - El-Mastouri, Zakia; Košnarová, Pavlína; Hamouzová, Kateřina; Alimi, Ezzedine; Soukup, Josef (Frontiers in Plant Science, 2024)
Rigid ryegrass (Lolium rigidum Gaud.) is one of the most troublesome weeds in Moroccan and Tunisian cereal crop fields. Nineteen rigid ryegrass field populations were randomly selected in northern wheat crop areas of Morocco and Tunisia to examine the patterns of herbicide resistance to acetolactate synthase (ALS) and acetyl-CoA carboxylase (ACCase) -inhibiting herbicides. Greenhouse experiments confirmed reduced sensitivity to ALS and/or ACCase-inhibiting herbicides in all L. rigidum populations. Occurrence of target site resistance (TSR) was tested using high-throughput genotyping. The advent of next-generation sequencing (NGS) has enabled easy identification of causal mutations and confirmed the presence of ALS and ACCase mutations at specific codons conferring TSR. Thirteen populations showed resistance to ALS-inhibiting herbicides associated with point mutations in positions Thr-